2010
DOI: 10.1523/jneurosci.4962-08.2010
|View full text |Cite
|
Sign up to set email alerts
|

TheN-Glycanasepng-1Acts to Limit Axon Branching during Organ Formation in Caenorhabditis elegans

Abstract: Peptide:N-glycanases (PNGases) are cytoplasmic de-N-glycosylation enzymes that have been shown in cultured cells to facilitate the degradation of misfolded glycoproteins during endoplasmic reticulum-associated degradation and in the processing of major histocompatibility complex class I antigens for proper cell-surface presentation. The gene encoding PNGase activity was initially described in budding yeast (Png1p) and shown to be highly conserved from yeast to humans, but physiological roles in higher organism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 52 publications
1
25
0
1
Order By: Relevance
“…Although Png1 mutants in budding yeast (9) or in plants (42) did not show any significant phenotypic consequences, more recent studies suggests that PNGase orthologs may play important physiological roles in other eukaryotes (43)(44)(45)(46). Recent exome analysis studies have identified human patients with mutations in the NGLY1 gene (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Although Png1 mutants in budding yeast (9) or in plants (42) did not show any significant phenotypic consequences, more recent studies suggests that PNGase orthologs may play important physiological roles in other eukaryotes (43)(44)(45)(46). Recent exome analysis studies have identified human patients with mutations in the NGLY1 gene (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…76 In mammalian PNGase this PUB domain is responsible for ERAD substrate interaction. 69 Thus, the role of PNG-1 in ERAD substrate processing remains to be demonstrated. 76 Like the homologous proteins in humans, mouse and yeast, PNG-1 also contains the transglutaminase domain, which is required for PNGase function.…”
Section: Png-1 Is a N-glycanase With Disulfide Reductase Activitymentioning
confidence: 99%
“…PNG-1 has been described to act in axon branching, which could be dependent on its PNGase and thioredoxin domain. 69 Using png-1 lossof-function mutants, an increased axon branching was observed. 69 PNG-1, together with its putative interaction partner RAD-23, may process retro-translocated glycopeptides in the cytosol and form bioactive peptides, which are involved in the inhibition of axon branching.…”
Section: Png-1 Is a N-glycanase With Disulfide Reductase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Des mutants de délétion du gène PNG1 chez Drosophila melanogaster montrent un arrêt ou un ralentissement du développement et une stérilité [29]. La délétion du gène PNG1 entraîne des défauts de polarisation pendant la croissance hyphale du champignon Neurospora crassa [30] et pendant la croissance neuronale chez Caenorhabditis elegans [31]. Ces activités morphogéniques de la PNGase sont indé-pendantes de son activité de déglycosylation : les protéines Png1p de Drosophila melanogaster et de Neurospora crassa sont en effet inactives par défaut d'un motif CXXC (D. melanogaster) [29] ou par l'absence d'un des acides aminés de la triade catalytique (N. crassa) [30].…”
Section: Png1 Joue Un Rôle Dans La Mise En Place De La Polarité Celluunclassified